Economic Policies and Agricultural Incentives: The Philippine Case - Cristina C. David (Philippine Institute for Development Studies (PIDS), 1995)
Despite implementation of structural adjustment programs, the agriculture sector has been continuously exhibiting a dismal performance. This paper analyzes the impact of economic policies on agricultural incentives from 1960-1992. Public expenditures for agricultural support services are also investigated.
Keywords: 330; agrarian reform; agriculture sector; price intervention; nominal protection rate; implicit tariff rate; levy